ACCOUNTING VALUES OF WOVEN FABRIC SMALL AND MEDIUM ENTERPRISES IN KLATEN INDONESIA - Pardi Pardi; Avita Ayu Fitria (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The research target is to examine and to analyze the use of accounting information for Small and Medium Enterprises (SMEs) on woven fabrics from the following aspects: manager decisions, business scale, business significances, and business liabilities. The samples of woven fabric Small and Medium Enterprises population in Klaten were collected using purposive sampling obtained from 50 respondents. The data collection was done through interviews and questionnaires, while they were analyzed using multiple linear regression test. The results of the test of business scale and business significances have an impact on the use of accounting information, but managers' decisions and business liabilities do not affect the use of accounting information by woven fabric Small and Medium Enterprises. Keywords: Accounting Value, Small and Medium Enterprise, Woven Fabric